Pengaruh Self-efficacy Terhadap Job Satisfaction Melalui Work Engagement pada Karyawan PT Pelayaran Nasional Indonesia (Persero) Surabaya - Adinda Nur Latifa Putri; Agus Frianto (Jurnal Ilmu Manajemen, 2022)
This study aims to analyse the effect of self-efficacy on job satisfaction through job involvement. This study uses a quantitative approach with a purposive sampling method. The respondents were 40 employees of a state-owned company engaged in water transportation services. Statistical analysis in this study used the Structural Equation Model (SEM) with SmartPLS 3 software as a data processing tool. The results showed that self-efficacy had no effect on job satisfaction but positively and significantly affected job involvement. Self-efficacy does not significantly affect job satisfaction through work engagement as an intervening variable. Companies should consider improving the management of existing human resources so that employees feel comfortable and more motivated at work, such as providing facilities to strengthen relationships between employees and their health. Then, the company can enforce a promotion system arrangement based on competence or achievement that has met the service requirements. It will encourage employees to excel and feel satisfied with their work.